EXPERIMENTAL STUDY OF THE DIELECTRIC BEHAVIOR OF TINIDAZOLE IN ACETONE AT 25°C - CASTILLO, María V.; CHECA, María A.; MANZUR, María E.; FERRETTI, Ferdinando H.; VARGAS, Edgar F.; MARTÍNEZ R., Fleming; YURQUINA, Alicia (Vitae, 2010)
Tinidazole is an anti-parasitic drug widely used nowadays in therapeutics. Nevertheless, it has not been well characterized from a physicochemical point of view. In this context, by means of optical experimental methods and dielectric spectroscopy applied to diluted solutions of Tinidazole in Acetone, molar polarizations of the solute, 0P2, and the solvent, 0P1, and the average dipolar moment of tinidazole associated to acetone, were estimated, resulting in 9.18 D. Since this value is higher than the theoretical m of the two main conformers of isolated tinidazole, that is, 3.22 and 4.29 D, respectively, the formation of interactions between the solute and the solvent is assumed. An effect of intermolecular association by van der Waals and hydrogen bond interactions conducting to a modification of the partial molar volume of the solute is thus expected. From the experimental and analysis by using the Halverstadt-Kumler’s method, it can be seen that the partial molar volume had a 24% reduction as compared with the theoretical value, which would confirm the presence of such interactions.